The Phenomenon Of Faceapp Applications, Hadiths’s Perspectives: An Analyses of Taṣhwīr Hadith Using Yusuf Qardhawi's Hermeneutics - Syahridawaty Syahridawaty (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2021)
The popularity of various gadget applications such as faceapp has indicated a significant technological developments. As a consequence, this application raises the pros and cons among social media users, each of the ideas provides certain convincing arguments. Those who competing the use of such app use a thematic hadith about taṣwīr to support their arguments. This library studies discusses the hadith being used by the contending voice of the faceapp, that is the taṣwīr hadith. The result shows that the use of hadith taṣwīr for the bases of the refusal of faceapp is not connected to the principle of the hadith idea, that is changing faces become older or younger to personal photos. In addition to the fact that none of the majority of scholars concerned with the photos. The author found three significance conclusions in the hadith: The first is the device to always worship God with full obedience and make distance from all forms of shirk. The second reason is to always instill the nature of laughter in the heart, which is to humble yourself before God and consider all strength and greatness only belongs to God. And the last intention is always doing what God has blessed and leaving what invites his wrath.